Upaya Meningkatkan Minat Belajar Siswa Dengan Model Pembelajaran Problem Based Learning Pada Materi Kemampuanku Terbatas Kelas VII di SMPN 1 Sanaman Mantikei - Yohana Godelifa Nago (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Students' interest in learning is something that is important in the smooth teaching and learning process. Students who have high interest in learning in the learning process can support the teaching and learning process to improve, and vice versa, if students have low interest in learning, the quality of learning will decrease and this will affect learning outcomes. Slameto (1995: 57) explains that interest is "a high inclination towards something". Interest is a characteristic that persists in a person. Interest is a persistent interest or tendency to pay attention to or be involved in something because you realize the importance or value of that thing. Learning models have a very important role because learning models are a means of conveying lesson material. Without the right model, a learning process will not take place effectively and efficiently. This learning model must be able to involve all students to play an active role in the learning process, be able to develop students' ability to think critically so that the learning process becomes more interesting and enjoyable while also being able to foster students' interest in learning so that student learning achievement is expected to increase. In reality, realizing an active and enjoyable learning process as stated above is not easy. The same thing happens when studying Catholicism. Learning Catholic Religion feels uninteresting because there are several factors in the teaching and learning process, including facilities and infrastructure, learning models, and a learning environment that is less effective and enjoyable because there is no room for religious lessons, so the activity process is disrupted because they have to move around appropriately. , other supporting facilities such as internet networks and electricity networks are not available, so learning is not centered on students but more on teachers lecturing, so students' interest in learning decreases. Ideally, a learning process requires appropriate strategies, especially in learning Catholicism, which has been designed. Thus, learning must be able to provide provisions for students to have good character, develop faith, think critically and be creative. To provide provisions for students, Catholic Religion learning is needed that is innovative, interesting and fun for students so that Catholic Religion subjects are no longer considered boring subjects which will impact students' low interest in learning Catholic Religion lessons. Based on the existing problem formulation, the aim to be achieved in this research is that the use and implementation of the problem based learning model can increase students' interest in learning in class VII Catholic Religious Lessons, the material My Capabilities Are Limited at SMP Negeri 1 Sanaman Mantikei. The type of research used in this research is descriptive qualitative research. This research is classroom action research carried out in two cycles offline. The use of the Problem Based Learning Model that matches the syntax in learning Catholic Religious Education in class VII of SMP Negeri 1 Sanaman Mantikei is very effective in increasing students' interest in learning. Increased student learning can be seen in initial conditions where student interest in learning is low, then interest in learning increases after being given action.